2019
DOI: 10.2147/idr.s223597
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incidence, Bacterial Profiles, And Antimicrobial Resistance Of Culture-Proven Neonatal Sepsis In South China</p>

Abstract: BackgroundNeonatal sepsis (NS) is one of the leading causes of infant morbidity and mortality, but little is known about pathogen incidence and distribution in China.MethodsIn this retrospective study (January 2012 to December 2016), culture-proven cases aged less than 28 days with diagnosed NS in the Guangzhou Women and Children’s Medical Center, South China, were analyzed for pathogen incidence and antimicrobial resistance.ResultsA total of 620 isolates were identified from 597 NS cases. Gram-negative bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
(41 reference statements)
11
16
2
Order By: Relevance
“…E coli was an important GNP in low-income settings and was the second most common early-onset BSI pathogen in a large US prospective cohort study (17). Similar to recent reports from Chinese and other Asian counties, GNP predominated in the pathogens causing EOS in our study, with the top one E. coli responsible for 27.2% (17,22,23). GBS was second common pathogen of EOS accounting for 14.6%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…E coli was an important GNP in low-income settings and was the second most common early-onset BSI pathogen in a large US prospective cohort study (17). Similar to recent reports from Chinese and other Asian counties, GNP predominated in the pathogens causing EOS in our study, with the top one E. coli responsible for 27.2% (17,22,23). GBS was second common pathogen of EOS accounting for 14.6%.…”
Section: Discussionsupporting
confidence: 86%
“…We found that K pneumonia was the most frequently pathogen with hospital-acquired LOS, followed by E. coli, which is parallel with the results of a latest study in south China (23). Meanwhile, CoNS was the third common pathogen causing LOS accounting for 11.2%, with majority of identi ed from VLBW.…”
Section: Discussionsupporting
confidence: 85%
“…In current study, about two thirds of pathogens identi ed were responsible for HALOS. Approximately 60% of HALOS were due to GNB which was similar to the results from previous Chinese studies (21,22). A review of 11,471 bloodstream samples indicated that GNB was detected from no less than 60% of positive blood cultures in all the developing settings of the world (23).…”
Section: Discussionsupporting
confidence: 85%
“…Another remarkable nding in the Chinese NICUs was the relatively high percentage of fungi in HALOS. Nearly all the identi ed fungi infections were responsible for HALOS, which was paralleled with other Chinese studies (21,22). Similarly, recent studies have also reported outbreaks of fungal nosocomial infection in Chinese NICUs which alerted clinicians (26,27).…”
Section: Discussionsupporting
confidence: 63%
“…A previous meta-analysis reported that Staphylococcus species, especially Coagulase negative Staphylococcus ( CoNS ) continue to be the principal organisms of neonatal sepsis in China [ 10 ]. Nevertheless, more recent data described Klebsiella pneumoniae as the most frequent pathogen, with widespread antimicrobial resistance (AMR) [ 11 ]. Klebsiella pneumoniae was primarily associated with LOS, greater morbidity, mortality and limited treatment options in neonates [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%